1993
DOI: 10.1111/j.1439-037x.1993.tb00437.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Thiourea, Thiamine and Ascorbic Acid on Growth and Yield of Maize (Zea mays L.)

Abstract: Three chemicals, viz., thiourea, thiamine and ascorbic acid capable of potentiating-SH turnover, were tested with the objective to improve growth and productivity of maize. Thiourea was tested as seed-soaking and foliar-applied treatments as also in combination. Thiamine and ascorbic acid were tested as foliar sprays alone. Foliar treatments were applied at vegetative stage (30 and 45 days after sowing).The results of the field experiment showed that seed soaking with thiourea (500 ppm) tended to improve grain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
1

Year Published

1996
1996
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 11 publications
3
38
1
Order By: Relevance
“…In the current study, F v / F m of both maize cultivars increased due to exogenously applied TU under saline conditions, which is parallel to the findings of Pandey et al (2013), who documented improved chlorophyll fluorescence in salt stressed Indian mustard (Brassica juncea) plants due to exogenously applied TU and they attributed this growth improvement to TU-induced high efficiency of PSI and PSII. About two decades ago, Sahu et al (1993) observed that exogenously applied TU enhanced the photosynthetically active leaf area as well as the rate of photosynthesis in maize plants, which was ascribed to TU-induced improvement in the efficiency of photosystems. To date, a number of experiments have been carried out on TU-induced changes/improvement in the rate of photosynthesis under stress in different crops, e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current study, F v / F m of both maize cultivars increased due to exogenously applied TU under saline conditions, which is parallel to the findings of Pandey et al (2013), who documented improved chlorophyll fluorescence in salt stressed Indian mustard (Brassica juncea) plants due to exogenously applied TU and they attributed this growth improvement to TU-induced high efficiency of PSI and PSII. About two decades ago, Sahu et al (1993) observed that exogenously applied TU enhanced the photosynthetically active leaf area as well as the rate of photosynthesis in maize plants, which was ascribed to TU-induced improvement in the efficiency of photosystems. To date, a number of experiments have been carried out on TU-induced changes/improvement in the rate of photosynthesis under stress in different crops, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…To date, a number of experiments have been carried out on TU-induced changes/improvement in the rate of photosynthesis under stress in different crops, e.g. clusterbean (Burman et al, 2004), wheat (Nathawat et al, 2007), and maize (Sahu et al, 1993), but the role of TU in efficiency of photosystems has not been well researched. It is well known that the efficiency of photosystems and rate of photosynthesis are closely interlinked (Misra et al, 2006;Geissler et al, 2009;Ashraf and Harris, 2013), but the information on TUinduced changes in the photosynthesis linked to either PSI or PSII still needs to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…The enhancement in harvest index of niger may be due to better dry matter partitioning as reported by Parihar et al, (1988), Sahu et al, (1993) and Sharma (2002). Table.2 Effect of thiourea on oil content of niger and Dehydrogenase activity in soil…”
Section: Resultsmentioning
confidence: 52%
“…The increase in yield due to thiourea application is a clear reflection of increase in growth and yield attributes. The yield increase by the application thiourea may due to the beneficial effect of thiourea on seed germination, seedling growth, chlorophyll content, protein content, biomasss production and better dry matter partitioning as reported by Parihar et al, 1988;Sahu et al, 1993 andSharma, 2002. In sulphur containing amino acids, there is a breakdown of SH group into S and H under stress situations.…”
Section: Resultsmentioning
confidence: 94%
“…Thiourea is a sulphahydral compound and help to improve productivity and its role as a drought tolerant is well established under the arid and semi-arid regions (Sahu et al, 1993).Thiourea have 42% sulphur and 36 % of nitrogen. Thus, it behaves in physiology of plants both as a sulphahydryl compound and as an amino compound like urea (Garg et al, 2006).…”
Section: Issn: 2319-7706 Volume 6 Number 3 (2017) Pp 2556-2560mentioning
confidence: 99%